2011
DOI: 10.1029/2010gl046016
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of liquid dependent ice nucleation in high-latitude stratiform clouds from surface remote sensors

Abstract: [1] Ground-based lidar, radar and microwave radiometer observations at Eureka, Canada, Barrow, Alaska and over the western Arctic Ocean measure physical characteristics and morphology of stratiform clouds. Despite transition of a cold atmosphere (−15 C)through ice supersaturated conditions, ice is not observed until soon after a liquid layer. Several cases illustrating this phenomenon are presented in addition to long-term observations from three measurement sites characterizing cloud phase frequency. This ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
222
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(233 citation statements)
references
References 28 publications
10
222
0
1
Order By: Relevance
“…However, a number of field and modelling studies have indicated that in mixed-phase clouds water saturation is a prerequisite for the formation of ice, suggesting that deposition mode nucleation or condensation below water saturation may be of limited importance for such clouds (Field et al, 2012;Twohy et al, 2010;Ansmann et al, 2009;de Boer et al, 2011;Westbrook and Illingworth, 2011). Consequently both immersion and contact modes are expected to dominate ice formation in mixed-phase clouds (Hoose et al, 2010b).…”
Section: O'sullivan Et Al: Ice Nucleation By Fertile Soil Dustsmentioning
confidence: 99%
“…However, a number of field and modelling studies have indicated that in mixed-phase clouds water saturation is a prerequisite for the formation of ice, suggesting that deposition mode nucleation or condensation below water saturation may be of limited importance for such clouds (Field et al, 2012;Twohy et al, 2010;Ansmann et al, 2009;de Boer et al, 2011;Westbrook and Illingworth, 2011). Consequently both immersion and contact modes are expected to dominate ice formation in mixed-phase clouds (Hoose et al, 2010b).…”
Section: O'sullivan Et Al: Ice Nucleation By Fertile Soil Dustsmentioning
confidence: 99%
“…At warmer temperatures, ice particles may coexist with supercooled droplets, due to heterogeneous nucleation facilitated by the presence of ice nucleating particles (INPs) (Cantrell and Heymsfield, 2005). In cases where INPs are immersed in the droplet before supercooling, referred to as immersion freezing mechanism, the droplets first grow to supercritical size before freezing occurs (de Boer et al, 2011). Observations and modeling studies suggest that immersion freezing is the prominent mechanism for heterogeneous ice formation in mixed phase clouds (Rosenfeld and Woodley, 2000;Ansmann et al, 2008;Field et al, 2012;Nagare et al, 2016;Possner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Contact freezing occurs when a solid particle collides with a supercooled liquid droplet, resulting in ice nucleation. Immersion mode and contact freezing are thought to be most important in many mixed phase clouds (Lohmann and Diehl, 2006;de Boer et al, 2010). Nucleation of ice or droplets directly from the vapour phase without the need for aerosol is not thought to be important in the troposphere, but may be important in the mesosphere (Murray and Jensen, 2010).…”
Section: Introductionmentioning
confidence: 99%